Marine cyanobacteria as potential alternative source for GABA production. (December 2019) - Shiels, Katie; Murray, Patrick; Saha, Sushanta Kumar
Abstract: GABA (γ-aminobutyric acid) is a non-proteinogenic amino acid that plays a significant role in various health functions and has been identified in cyanobacteria. This investigation screened seventeen fast-growing Irish marine cyanobacteria as potential sustainable producers of GABA. Twelve of the seventeen cyanobacteria tested positive for GAD (glutamate decarboxylase) activity in vitro and were tested for their GABA content using a spectrophotometric assay. Five of the twelve cyanobacterial extracts ( Calothrix contarenii SABC022701, Chlorogloea microcystoides SABC022904, Phormidium africanum SABC010301, P . angustissimum SABC022612 and P . laminosum SABC022613) showed the characteristic GABA peak with the amounts of GABA produced ranging from 0.99 × 10 4 to 72.84 × 10 4 nmol g − 1 dry-weight biomass. These five cyanobacterial extracts were resolved by thin layer chromatography (TLC) to identify the GABA band, and the GABA bands from unstained TLC plate (same Rf values) were excised for verification of GABA spectrophotometrically. This is the first report on five potential Irish marine cyanobacteria as GABA producers. Graphical abstract: Unlabelled Image Highlights: Identified five marine cyanobacteria as potential producers of GABA Irish marine cyanobacteria screened for potential producers of GABA Twelve out of seventeen cyanobacteria proved positive for GAD activity. GABA was detected both spectrophotometrically and by thin layer chromatography. GABA concentrations were ranging from 0.99 × 10 4 to 72.84 × 10 4  nmol g − 1 dry weight biomass.